Maternal adverse childhood experiences on child growth and development in rural Pakistan: An observational cohort study. - Esther O Chung; Elissa Scherer; Katherine LeMasters; Lisa Bates; Ashley Hagaman; Brooke S Staley; Lauren C Zalla; Siham Sikander; Joanna Maselko (PLOS Global Public Health, 2023)
Maternal adverse childhood experiences (ACEs) have significant impacts on the next generation with links to negative birth outcomes, impaired cognitive development, and increased socioemotional problems in children. However, not all types or levels of adversity are similarly deleterious and research from diverse contexts is needed to better understand why and how intergenerational transmission of adversity occurs. We examined the role of maternal ACEs on children's growth, cognitive, and socioemotional development at 36 months postpartum in rural Pakistan. We used data from 877 mother-child dyads in the Bachpan Cohort, a birth cohort study. Maternal ACEs were captured using an adapted version of the ACE-International Questionnaire. Outcomes at 36 months of age included child growth using the WHO growth z-scores, fine motor and receptive language development assessed with the Bayley Scales of Infant and Toddler Development, and socioemotional and behavioral development measured with the Ages and Stages Questionnaire: Socioemotional and Strengths and Difficulties Questionnaire. To estimate the associations between maternal ACEs and child outcomes, we used multivariable generalized linear models with inverse probability weights to account for sampling and loss to follow-up. Over half of mothers in our sample (58%) experienced at least one ACE. Emotional abuse, physical abuse, and emotional neglect were the most commonly reported ACEs. We found null relationships between the number of maternal ACEs and child growth. Maternal ACEs were associated with higher fine motor and receptive language development and worse socioemotional and behavioral outcomes. Maternal ACE domains had similarly varying relationships with child outcomes. Our findings highlight the complexity of intergenerational associations between maternal ACEs and children's growth and development. Further work is necessary to examine these relationships across cultural contexts and identify moderating factors to mitigate potential negative intergenerational effects.